1981
DOI: 10.1136/adc.56.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Prader-Willi Syndrome after age 15 years.

Abstract: SUMMARY Twenty-four patients, all of them over 15 years, with the Prader-Willi syndrome are described. Obesity, often extreme, associated with an insatiable appetite, was their principal handicap and this was made worse by educational subnormality and hypogonadism. Three of them developed diabetes. Each attended a special school or an adult training centre. Although most of them were of short stature and had scoliosis, 2 were tall but they were even more severely mentally retarded than is usually the case. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
1
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 31 publications
0
82
1
1
Order By: Relevance
“…Decreased physical exercise and lowered energy expenditure have been identified as exacerbating the problem (Butler, 1990;Davies & Joughin, 1993). Physical health problems associated with weight gain have been reported including: diabetes mellitus (Laurance et al, 1981), coronary artery disease (Lamb & Johnson, 1987) and premature death (Laurance et al, 1981). The psychological impact of being overweight may also be detrimental, contributing to difficulties in forming relationships with peers (Dykens et al, 1992) and in turn affecting an individuals' selfworth (Wolfensberger, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased physical exercise and lowered energy expenditure have been identified as exacerbating the problem (Butler, 1990;Davies & Joughin, 1993). Physical health problems associated with weight gain have been reported including: diabetes mellitus (Laurance et al, 1981), coronary artery disease (Lamb & Johnson, 1987) and premature death (Laurance et al, 1981). The psychological impact of being overweight may also be detrimental, contributing to difficulties in forming relationships with peers (Dykens et al, 1992) and in turn affecting an individuals' selfworth (Wolfensberger, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Ventilatory failure appears to be a frequent cause of death but this has hardly been investigated. In one series of 33 patients, nine died and in each case cardiorespiratory failure was given as the cause of death, although no details of the clinical features or treatment were available [3].…”
Section: Discussionmentioning
confidence: 99%
“…1,[8][9][10][11][12] One study estimated that between 43% and 66% of those with PWS developed scoliosis. 8 The Queen Elizabeth Hospital for Children in London did a retrospective study that demonstrated that 62% of PWS patients had clinical scoliosis.…”
Section: Introductionmentioning
confidence: 99%
“…8 The Queen Elizabeth Hospital for Children in London did a retrospective study that demonstrated that 62% of PWS patients had clinical scoliosis. 9 Body composition studies have shown increased body fat and reduced muscle in PWS, both in infants and adults. These 2 factors are most likely major contributors in the development and prevalence of scoliosis among those with PWS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation